Hicrî ikinci asırda Yemen'de hadis - Demirci, Hatice (My University, 2021)
Yemen, hicrî 2. asrın önemli ilim merkezlerinden olan Medine, Kûfe ve Basra kadar hadis rivayetinde merkezî bir rol oynamasa da nispeten uzak bir coğrafyada bulunmasına rağmen, özellikle Ma‘mer b. Râşid’in ilim tahsili için bölgeye yerleşmesi ve sonrasında başlayan rihle faaliyetleriyle birlikte ilmî anlamda bir ivme kazanmıştır. Bu çalışmada hadis ilmi açısından Yemen’in 2/ 8. asırdaki durumunu, bölgede mevcut hadis halkalarını ve bu halkaların mahiyetini tespit etmek amaçlanmıştır. Bu doğrultuda Tâvûs ve Ma‘mer’in sistemli birer halkaları olduğu tespit edilmiş ve bu halkaların özellikleri incelenmiştir. Halkaların kurucu isimlerinin özellikle hadis usulü konularında sergiledikleri tutumların, diğer halka üyeleri tarafından devam ettirilip ettirilmediği takip edilmiştir. Böylelikle hadis tasnif faaliyetinde önemli bir yere sahip olan Yemen’in, erken dönemde hadis tarihi açısından ilmî anlamda ne derece etkin olduğu tartışılmıştır.

Although Yemen did not play a central role in the narration of hadith as much as Madina, Kufa and Basra which were important centers of knowledge in the second century AH and it was located in a relatively distant region, it came into prominence especially after Maʻmar ibn Rāshid settled in the region to pursue knowledge and the journeys undertaken in pursuit of knowledge (riḥla) that began afterwards. In this study, the situation of Yemen in the second century AH in terms of the science of hadith, existing circles of hadith studies and the nature of these circles are aimed to be determined. In this direction, it has been determined that Ṭāvus and Ma'mer each have systematic circles and the features of these circles have been examined. It has been followed whether the attitudes of the founding names of the circles, especially on the issues of hadith method, were continued by the other circle members or not. Thus, it was discussed how effective and active Yemen was (being an important place in the classification of hadith) in terms of the history of hadith in the early period of Islam.
Keywords: Abdürrezzâk; Circles; Hadis; Hadith; Halka; Hişâm b. Yusuf; Hişâm b. Yusuf Yemen; Islam; İbn Münebbih; İslam; Ma‘mer; Tâvûs; Yemen